Analysis of Marketing Strategies in Increasing Sales on Zeribowl Dessert Kitchen Asia Branch Mega Mas Field - Muharmansyah R Maulana, ahmad; Annio Indah Lestari Nasution; Aqwa Naser Daulay (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine marketing strategies that can be implemented to improve marketing performance at Zeribowl Dessert using the SWOT analysis method. This research method uses a qualitative method with a descriptive approach with data collection methods through documentation studies, observations, interviews and questionnaires obtained from 30 customers and 4 Zeribowl Dessert staff. The research results show that the Strength and Opportunities (SO) value is 3.23. Then the Weakness and Threats (WT) value is 3.6. Thus the researcher concludes that an aggressive strategy can be carried out by maximizing strength by taking advantage of Zeribowl's opportunities to gain profits through marketing strategies that can be implemented by Zeribowl Dessert, including; market development and market penetration, product development, market target and market positioning.